2020
DOI: 10.3389/fcimb.2020.591974
|View full text |Cite
|
Sign up to set email alerts
|

Cytological and Histopathological Spectrum of Histoplasmosis: 15 Years of Experience in French Guiana

Abstract: nodes were positive in 42 specimens (31 histology and 11 cytology). Histopathological analysis of the 31 lymph nodes showed a variable histological appearance. Tuberculoid forms were most frequent (24/31, 77,4%).Conclusions: From the pathologist perspective, this is the largest series to date showing that digestive involvement was the most frequent, usually with a tuberculoid form and a greater load of Histoplasma. With awareness and expertise, cytology and pathology are widely available methods that can give … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…In our Histoplasmosis pathology experience, 31 patients had histological confirmation of lymph node histoplasmosis by the presence of H. capsulatum yeasts on lymph node biopsies or surgical specimens. Interestingly and consistently with the clinical outcome of this study the granulomatous inflammatory reaction of tuberculoid type was the most frequent (24/31, 77.4%) which usually corresponds to effective tissue response ( Drak Alsibai et al., 2020 ). Among these 24 granulomatous cases, histological variants perfectly mimicking tuberculosis with epithelioid granulomas, multinucleated giant cells and caseous necrosis were found in 10 cases, followed by less typical epithelioid granulomatous variants where giant cells and necrosis were absent in eight cases, then by forms with predominant macrophage infiltration in six cases.…”
Section: Discussionsupporting
confidence: 86%
“…In our Histoplasmosis pathology experience, 31 patients had histological confirmation of lymph node histoplasmosis by the presence of H. capsulatum yeasts on lymph node biopsies or surgical specimens. Interestingly and consistently with the clinical outcome of this study the granulomatous inflammatory reaction of tuberculoid type was the most frequent (24/31, 77.4%) which usually corresponds to effective tissue response ( Drak Alsibai et al., 2020 ). Among these 24 granulomatous cases, histological variants perfectly mimicking tuberculosis with epithelioid granulomas, multinucleated giant cells and caseous necrosis were found in 10 cases, followed by less typical epithelioid granulomatous variants where giant cells and necrosis were absent in eight cases, then by forms with predominant macrophage infiltration in six cases.…”
Section: Discussionsupporting
confidence: 86%
“…In HIVinfected patients, all BALs were macrophage-dominant. In a recent experiment concerning the histological appearance of histoplasmosis, we demonstrated that the macrophagepredominant microenvironment is the most frequent in HIV patients [12]. This microenvironment is represented by two histological forms: the granulomatous (or tuberculoid) form and the intermediate form.…”
Section: Discussionmentioning
confidence: 86%
“…These two forms are rich in macrophages or epithelioid cells derived from macrophages. In addition, in the anergic form and the sequelae form, the host inflammatory responses to H. capsulatum are very weak [12]. Nevertheless, it should be remembered that BAL is a medium naturally rich in alveolar macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations